A Purification Method of 18F-FP-(+)-DTBZ via Solid-Phase Extraction With Combined Cartridges - Dai, Yuyin; Sa, Ri; Guan, Feng; Wang, Qi; Li, Yinghua; Zhao, Hongguang (Frontiers in Medicine, 2021)
Abstract Background: To optimize [18F] 9-fluoropropyl-(+)-dihydrotetrabenazine (18F-FP-(+)-DTBZ) purification via solid-phase extraction (SPE) with combined cartridges to facilitate its widespread clinical application. Methods: A modified SPE purification method, employing Sep-Pak PS-2 and Sep-Pak C18 cartridges, was used for the preparation of 18F-FP-(+)-DTBZ. This method was compared to the purification method of high-pressure liquid chromatography (HPLC) and SPE with one cartridge, following quality control test and positron emission tomography (PET) imaging in healthy volunteers and patients with parkinsn's disease (PD) . Results: A SPE purification method integrating Sep-Pak PS-2 and Sep-Pak C18 cartridges was implemented successfully. The retention time of 18F-FP-(+)-DTBZ purified by HPLC, SPE with Sep-Pak PS-2, SPE with Sep-Pak C18, and SPE with combined use of Sep-Pak PS-2 and Sep-Pak C18 cartridges was 8.7 min, 8.8 min, 8.7 min, and 8.9 min, respectively. Fewest impurity peak was detected in 18F-FP-(+)-DTBZ purified by the SPE with combined use of Sep-Pak PS-2 and Sep-Pak C18 cartridges. This modified SPE purification method provided a satisfactory radiochemical yield of 29 ± 1.8% with radiochemical purity > 99% and shortened synthesis time to 27 min. The brain uptake of 18F-FP-(+)-DTBZ purified by the modified SPE was comparable to that purified by HPLC in both healthy volunteers and PD patients. Conclusions: A SPE method integrating Sep-Pak PS-2 and Sep-Pak C18 cartridges for purification of 18F-FP-(+)-DTBZ may be highly suited to automatic synthesis for routine clinical applications, as it provides excellent radiochemical purity, high yield as well as operational simplicity.